INVESTIGATION OF MORPHOLOGY AND POROUS STRUCTURE OF MEDICAL CLAYS - E. T. Zhilyakova; A. V. Bondarev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents the results of the research of morphology and porous structure of medical clays. The specific surface area, volume of pores and the average size of pores were identified.